Lithium-rich manganese-based positive electrode composite material as well as preparation method and application thereof

By modifying the surface of a single crystal lithium-rich manganese-based positive electrode material to form a lithium borate surface cladding layer, the problems of structural instability and side reactions of the material during circulation are solved, and higher electrochemical performance and lower production costs are achieved.

CN119812256APending Publication Date: 2025-04-11SOUTHWEST PETROLEUM UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411940414.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials are prone to interfacial side reactions during the circulation process, resulting in structural instability and affecting electrochemical performance. The traditional preparation methods are complex and time-consuming, resulting in increased material cost and energy consumption.

Method used

By modifying the surface of a single crystal lithium-rich manganese-based material with boric acid, a lithium borate surface coating is formed in situ, acting as a fast channel for lithium ions and alleviating the side reaction between the interface and the electrolyte.

Benefits of technology

It improves the cycling performance of the battery, improves the lithium-ion conductivity and rate performance of the material, and significantly improves capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812256A_ABST
    Figure CN119812256A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-rich manganese-based positive electrode composite material as well as a preparation method and application thereof, and belongs to the technical field of preparation of battery positive electrode materials. The preparation method comprises the following steps: (1) stirring and dissolving nickel salt, cobalt salt and manganese salt in water, and then stirring and mixing the nickel salt, the cobalt salt and the manganese salt with a precipitator and a complexing agent solution in a nitrogen atmosphere to obtain a precursor material; (2) uniformly mixing the precursor material, a lithium salt and a fused salt, and carrying out two times of calcination and annealing calcination to prepare a single crystal lithium-rich manganese-based material; and (3) adding the single crystal lithium-rich manganese-based material into a boric acid solution, and calcining to obtain the lithium borate in-situ coated lithium-rich manganese-based positive electrode composite material. Lithium borate formed on the surface of the lithium-rich manganese-based positive electrode material can promote lithium ion transmission and protect an interface at the same time, side reaction between the lithium borate and electrolyte is reduced, and the first coulombic efficiency and the cycling stability of the material are effectively improved. In addition, the method provided by the invention is simple and suitable for large-scale batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery positive electrode material preparation, and specifically relates to a lithium-rich manganese-based positive electrode composite material and a preparation method and use thereof. Background Art

[0002] The improvement of lithium-ion battery cathode materials is the key to achieving high energy density batteries. However, the actual capacity of commercial cathode materials is generally less than 200 mAh / g, which obviously cannot meet the growing demand. In this context, lithium-rich manganese-based cathode materials (xLi 2 MnO 3 (1-x)LiTMO 2 , where TM is Mn, Ni or Co) has become an ideal candidate material for the next generation of lithium-ion batteries due to its ultra-high specific capacity (up to 250 mAh / g) and high voltage (about 3.6 V). The high capacity of lithium-rich manganese-based cathode materials mainly comes from their unique anion redox reaction mechanism. However, this process includes both reversible and irreversible oxygen release, among which irreversible oxygen release will trigger interfacial side reactions, leading to irreversible structural changes, further inducing the formation of microscopic defects and cracks, and ultimately affecting the stability of the crystal structure and electrochemical performance, manifested as low first-cycle coulombic efficiency, continuous attenuation of capacity and voltage, and poor rate performance. These obstacles have seriously hindered the commercial application of lithium-rich manganese-based cathode materials.

[0003] At present, most lithium-rich manganese-based positive electrode materials are polycrystalline. Such materials will undergo significant expansion and contraction during the charge and discharge cycle, resulting in cracks inside the grains, further causing the breakage of secondary particles and increasing the occurrence of side reactions, leading to rapid decay of capacity and voltage. In contrast, single-crystal particles are not prone to breakage and dissolution during the cycle due to their superior mechanical strength, and therefore exhibit higher cycle stability and safety. In addition, the compaction density of single-crystal particles is high, which helps to improve the overall energy density of the battery. These characteristics make single-crystal lithium-rich manganese-based positive electrode materials a focus of attention in the development of high-performance lithium-ion batteries.

[0004] However, the current preparation methods of single-crystal lithium-rich manganese-based cathode materials usually rely on repeated calcination and molten salt-assisted processes, which are complicated and time-consuming, which not only increases production energy consumption, but also leads to increased material costs. In addition, traditional single-crystal materials often exhibit lower discharge specific capacity due to the increased transmission distance of lithium ions inside the particles. Therefore, it is particularly important to develop a simple, efficient preparation method for single-crystal lithium-rich manganese-based cathode materials with excellent electrochemical properties. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a lithium-rich manganese-based positive electrode composite material and a preparation method and use thereof. By modifying the surface of a single crystal lithium-rich manganese-based material with boric acid, a lithium borate surface coating layer is formed in situ, which can not only serve as a fast channel for lithium ions, but also alleviate the side reactions between the interface and the electrolyte during the cycle process, thereby improving the cycle performance of the battery.

[0006] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is: The object of the present invention is to provide a method for preparing a lithium-rich manganese-based positive electrode composite material, comprising the following steps: (1) stirring and dissolving nickel salt, cobalt salt and manganese salt in water to obtain a mixed metal salt solution, and then stirring and mixing the mixed metal salt solution with a precipitant and a complexing agent solution under a nitrogen atmosphere at 40 to 80° C. to obtain a precursor material through a coprecipitation reaction; (2) The precursor material, lithium salt and molten salt are mixed evenly, calcined at 300-700°C for 3-8h, then heated to 800-900°C, calcined for 5-15h, washed with water, and then annealed and calcined at 400-600°C for 1-8h to obtain a single crystal lithium-rich manganese-based material; (3) Add the single crystal lithium-rich manganese-based material to the boric acid solution, stir and evaporate the solvent, then heat up to 500-600°C at a rate of 1-10°C / min and calcine for 5-8h. After calcination, cool down to room temperature at a rate of 1-6°C / min to obtain a lithium-rich manganese-based positive electrode composite material in situ coated with lithium borate.

[0007] Furthermore, the molar ratio of the nickel salt, the cobalt salt and the manganese salt is 63:32:5.

[0008] Further, the nickel salt is one or more of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride; The cobalt salt is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate and cobalt chloride; The manganese salt is one or more of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

[0009] Furthermore, the concentration of the complexing agent is 0.2-2 mol / L, and the complexing agent is one or more of ammonia water, EDTA, citric acid, trisodium citrate and ethylenediamine.

[0010] Furthermore, the concentration of the precipitant is 1-6 mol / L, and the precipitant is one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate, oxalic acid and sodium oxalate.

[0011] Furthermore, the coprecipitation time is 12-24h, the reaction temperature is 40-80°C, and the pH value is 10.3-11.1.

[0012] Furthermore, the molar ratio of the precursor material, the lithium salt and the molten salt is 1:1.65~2.2:1~12.

[0013] Furthermore, the molar ratio of the precursor material, the lithium salt and the molten salt is 1:1.7~1.9:4~8.

[0014] Further, the lithium salt is one or more of lithium hydroxide and lithium oxide; The molten salt is any one or more of sodium chloride, potassium chloride, lithium chloride and hydrates thereof.

[0015] Furthermore, in step (2), the first calcination temperature is 500-600°C, and the time is 4-6 hours; the second calcination temperature is 800-900°C, and the time is 10-12 hours; the annealing calcination temperature is 400-500°C, and the time is 4-6 hours.

[0016] Furthermore, the calcination is performed in an oxygen-containing atmosphere, which includes an oxygen-containing atmosphere such as air.

[0017] Furthermore, in step (3), the weight ratio of boric acid to single crystal lithium-rich manganese-based material is 1:0.01-0.06.

[0018] Furthermore, the weight ratio of boric acid to the single crystal lithium-rich manganese-based material is 1:0.01~0.04.

[0019] Furthermore, the weight ratio of boric acid to the single crystal lithium-rich manganese-based material is 1:0.02~0.04.

[0020] Furthermore, in step (3), anhydrous ethanol is used as a solvent for dissolving boric acid.

[0021] Furthermore, in step (3), the heating rate is 4-6°C / min, and the cooling rate is 2-3°C / min.

[0022] Another object of the present invention is to provide a lithium-rich manganese-based positive electrode composite material, which is prepared by the above method.

[0023] Furthermore, the lithium-rich manganese-based positive electrode composite material also includes a conductive agent and a binder; wherein the content of the binder is ≤15wt%; and the content of the conductive agent is ≤15wt%.

[0024] Another object of the present invention is to provide a use of the above-mentioned lithium-rich manganese-based positive electrode composite material in the preparation of electrode materials or lithium-ion batteries.

[0025] The lithium-ion battery mentioned above of the present invention, in addition to comprising the lithium-rich manganese-based positive electrode composite material prepared by the present invention, other components, parts and structures can be existing technologies known in the art.

[0026] For example, the above lithium-ion battery comprises a positive electrode and a negative electrode which are compounded in sequence, wherein a separator and / or a solid electrolyte is arranged between the positive electrode and the negative electrode. In addition, in the battery, an electrolyte is also allowed to exist.

[0027] Beneficial effects of the present invention: When preparing the precursor material, nitrogen is introduced into the mixed metal salt solution. The nitrogen enters the salt solution and the metal ion solution to displace the oxygen in the solution, thereby preventing the metal ions from being oxidized during the solution preparation and precipitation reaction to produce small particle precursors, which affects the particle size distribution of the final product.

[0028] The present invention provides a new lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material, which can unexpectedly improve its electrochemical properties such as high capacity utilization and high and low temperature cycle stability based on the combined synergy of composition and structure.

[0029] The present invention innovatively evaporates the liquid phase of single crystal lithium-rich manganese-based material and boric acid in anhydrous ethanol and then anneals and calcines them in an oxygen-containing atmosphere, which can solve the problem of side reactions on the surface interface of the single crystal lithium-rich manganese-based material, successfully achieve in-situ coating of the surface of lithium borate, improve the lithium ion conductivity of the material, and improve the rate performance. The capacity and cycle stability of the prepared in-situ lithium borate in-situ coated lithium-rich manganese-based positive electrode composite material are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 X-ray diffraction patterns of the single crystal lithium-rich manganese-based material (marked as SCLLO) and the lithium-rich manganese-based positive electrode composite material (marked as SCLLOB) prepared in Example 1; Figure 2 A scanning electron microscope image of the lithium-rich manganese-based positive electrode composite material (labeled as SCLLOB) prepared in Example 1; Figure 3 HRTEM image of the lithium-rich manganese-based cathode composite material (labeled as SCLLOB) prepared in Example 1; Figure 4 XPS B 1s fine spectra of the single crystal lithium-rich manganese-based material (labeled as SCLLO) and the lithium-rich manganese-based positive electrode composite material (labeled as SCLLOB) prepared in Example 1; Figure 5 The cycle performance test results of the single crystal lithium-rich manganese-based material (marked as SCLLO) and the lithium-rich manganese-based positive electrode composite material (marked as SCLLOB) prepared in Example 1 after 200 cycles at 1C rate. DETAILED DESCRIPTION

[0031] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0032] Example 1 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0033] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0034] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0035] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0036] Example 2 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0037] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 60°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0038] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0039] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0040] Example 3 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0041] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.8 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0042] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0043] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0044] Example 4 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0045] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0046] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:8, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0047] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0048] Example 5 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 60:29:2, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0049] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0050] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.65:8, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0051] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0052] Example 6 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 66:35:8, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0053] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0054] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 600°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 800°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0055] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0056] Example 7 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0057] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0058] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 8h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 20h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0059] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0060] Example 8 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0061] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0062] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0063] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the washed, dried but not annealed single crystal lithium-rich manganese-based positive electrode material synthesized above and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 8 hours (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0064] Example 9 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0065] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0066] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0067] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 400°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 3 hours (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0068] Example 10 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0069] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0070] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0071] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.01 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0072] Embodiment 11 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0073] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0074] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and potassium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and potassium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0075] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.04 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0076] Example 12 A lithium-rich manganese-based positive electrode composite material in-situ coated with lithium borate, the preparation method of which is as follows: (1) Preparation of precursor Manganese sulfate, nickel sulfate and cobalt sulfate were used as raw materials, and the reaction raw materials were weighed according to the molar ratio of Mn:Ni:Co of 63:32:5, and deionized water was added to prepare a 2 mol / L metal salt solution.

[0077] The above solution was mixed with 2 mol / L sodium hydroxide solution in a continuous stirred tank reactor under N2 atmosphere. The temperature was 55°C and pH = 10.5 during the whole process. The precursor suspension was filtered, washed with deionized water, and then dried at 110°C for 24 hours to obtain a hydroxide precursor.

[0078] (2) Preparation of single crystal lithium-rich manganese-based materials The hydroxide precursor, lithium hydroxide and sodium chloride were weighed in a molar ratio of 1:1.75:4, placed in a mortar and mixed evenly, and then placed in a muffle furnace. In an air atmosphere (no directional airflow was formed), the temperature was increased from room temperature to 500°C (marked as T1) at a heating rate of 5°C / min, and the temperature was kept sintered for 5h (marked as t1), and then the temperature was increased to 900°C (marked as T2) at the same heating rate, and the temperature was kept sintered for 12h (marked as t2), and cooled to room temperature at a rate of 2°C / min, and the excess lithium hydroxide and sodium chloride were washed off with deionized water, and then annealed at 500°C (marked as T3) in a muffle furnace for 5h (marked as t3) to obtain a single crystal lithium-rich manganese-based positive electrode material (SCLLO).

[0079] (3) Preparation of lithium-rich manganese-based cathode composite materials coated with in-situ lithium borate Weigh 1 g of the above-synthesized single crystal lithium-rich manganese-based positive electrode material that has been washed, dried but not annealed, and 0.02 g of boric acid, dissolve the boric acid in 20 ml of anhydrous ethanol, add the single crystal lithium-rich manganese-based positive electrode material, stir and evaporate to dryness at 80°C, take it out and place it in a corundum crucible, then place it in a muffle furnace, sinter it in air, and heat it from room temperature to 500°C (marked as T4) at a heating rate of 5°C / min. After keeping it warm for 5h (marked as t4), cool it to room temperature at a rate of 2°C / min, take it out and grind it to obtain a lithium borate in-situ coated single crystal lithium-rich manganese-based positive electrode material (SCLLOB).

[0080] Comparative Example 1 Compared with Example 1, the only difference is that in step (2), lithium carbonate is used for high-temperature calcination, and other operations and parameters are the same as Example 1.

[0081] Comparative Example 2 Compared with Example 1, the only difference is that in step (2), lithium sulfate is used for high-temperature calcination, and other operations and parameters are the same as Example 1.

[0082] Comparative Example 3 Compared with Example 1, the only difference is that step (3) is omitted, and the single crystal lithium-rich manganese-based positive electrode material prepared in step (2) is directly used to perform electrochemical assembly measurement according to the method described later in the present invention.

[0083] Comparative Example 4 Compared with Example 1, the only difference is that in step (3), after dissolving boric acid in deionized water, the single crystal lithium-rich manganese-based positive electrode material prepared in step (2) is added and stirred to mix evenly, and then the solvent is evaporated to obtain a mixed material. Other operations and parameters are the same as in Example 1.

[0084] Comparative Example 5 Compared with Example 1, the only difference is that in step (3), after dissolving boric acid in anhydrous isopropanol, the single crystal lithium-rich manganese-based positive electrode material prepared in step (2) is added and stirred to mix evenly, and then the solvent is evaporated to obtain a mixed material. Other operations and parameters are the same as in Example 1.

[0085] Comparative Example 6 Compared with Example 1, the only difference is that in step (3), boric acid is directly ground and evenly mixed with the single crystal lithium-rich manganese-based positive electrode material prepared in step (2) to obtain a mixed material. Other operations and parameters are the same as in Example 1.

[0086] Test example 1. The single crystal lithium-rich manganese-based material (marked as SCLLO) and the lithium-rich manganese-based positive electrode composite material (marked as SCLLOB) prepared in Example 1 of the present invention were tested, and the test spectrum thereof is shown in Figures 1 to 4 .

[0087] like Figure 1 As shown in the XRD spectra, the SCLLO and SCLLOB cathode materials synthesized in Example 1 have sharp characteristic diffraction peaks, both of which belong to the α-NaFeO 2 The layered structure indicates that a single-crystal lithium-rich manganese-based positive electrode material with good crystallinity has been prepared.

[0088] like Figure 2 As shown in the SEM image, the morphology of the SCLLOB positive electrode material synthesized in Example 1 is a regular and smooth single crystal morphology, indicating the successful preparation of the single crystal lithium-rich manganese-based positive electrode material.

[0089] like Figure 3 As shown in the HRTEM image, the lithium borate synthesized in Example 1 in-situ coated single crystal lithium-rich manganese-based positive electrode material has a typical layered structure in its bulk phase, and a lithium borate coating layer appears on the surface.

[0090] like Figure 4 As shown in the results of XPS B1s, the lithium borate synthesized in Example 1 in-situ coated the single crystal lithium-rich manganese-based positive electrode material, indicating the presence of the boron element.

[0091] 2. Electrochemical performance test (1) Battery assembly The material prepared in the embodiment or comparative example of the present invention is used as an active material, and the active material is mixed with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) is added to grind into a slurry, which is coated on an aluminum foil with a scraper, dried, and cut into a positive electrode sheet; then assembled into a CR2032 button half-cell in an argon glove box (water <0.01ppm, oxygen <0.01ppm), wherein the positive electrode is the above-mentioned positive electrode sheet, the counter electrode is a lithium sheet, the diaphragm is Celgard 2500, and the electrolyte is ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 as a solvent, and 1.2 mol / L LiPF 6 A solution made of a solute.

[0092] (2) Battery performance test The BTS-5 V10 mA tester was purchased from Shenzhen Xinwei Electronics Co., Ltd. At 25°C, the charge and discharge cycle was performed at 0.1C (1C = 250mA / g) in the voltage range of 2.0V~4.8V for 3 weeks, and then the charge and discharge cycle was continued at 1C in the voltage range of 2.0V~4.8V for 200 cycles (200 turns). The test results are shown in Figure 5 .

[0093] 3. The lithium-rich manganese-based positive electrode materials of the above-mentioned Examples 1-12 and Comparative Examples 1-6 were tested at 25° C. The test results are shown in Table 1.

[0094] Table 1 Electrochemical properties of unmodified and modified lithium-rich manganese-based lithium battery cathode materials

[0095] According to Table 1 and Figure 5 It can be seen from the test results that the cycle stability of the in-situ lithium borate in-situ coated lithium-rich manganese-based positive electrode composite material prepared by the present invention is significantly better than that of the obtained single crystal lithium-rich manganese-based material.

[0096] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a lithium-rich manganese-based positive electrode composite material, characterized in that: The following steps are involved: (1) stirring and dissolving nickel salt, cobalt salt and manganese salt in water to obtain a mixed metal salt solution, and then stirring and mixing the mixed metal salt solution with a precipitant and a complexing agent solution under a nitrogen atmosphere at 40 to 80° C. to obtain a precursor material through a coprecipitation reaction; (2) The precursor material, lithium salt and molten salt are mixed evenly, calcined at 300-700°C for 3-8h, then heated to 800-900°C, calcined for 5-15h, washed with water, and then annealed and calcined at 400-600°C for 1-8h to obtain a single crystal lithium-rich manganese-based material; (3) Add the single crystal lithium-rich manganese-based material to the boric acid solution, stir and evaporate the solvent, then heat up to 500-600°C at a rate of 1-10°C / min and calcine for 5-8h. After calcination, cool down to room temperature at a rate of 1-6°C / min to obtain a lithium-rich manganese-based positive electrode composite material in situ coated with lithium borate.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the nickel salt, the cobalt salt and the manganese salt is 60-66:29-35:2-8.

3. The preparation method according to claim 1 or 2, characterized in that: The nickel salt is one or more of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride; The cobalt salt is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate and cobalt chloride; The manganese salt is one or more of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the precursor material, the lithium salt and the molten salt is 1:1.65~2.2:1~12.

5. The preparation method according to claim 4, characterized in that: The lithium salt is one or more of lithium hydroxide and lithium oxide; the molten salt is any one or more of sodium chloride, potassium chloride, lithium chloride, lithium sulfate and hydrates thereof.

6. The preparation method according to claim 1, characterized in that: In step (2), the first calcination temperature is 500-600°C and the time is 4-6 hours; the second calcination temperature is 800-900°C and the time is 10-12 hours; the annealing calcination temperature is 400-500°C and the time is 4-6 hours.

7. The preparation method according to claim 1, characterized in that: In step (3), the weight ratio of boric acid to single crystal lithium-rich manganese-based material is 1:0.01-0.

06.

8. The preparation method according to claim 1, characterized in that: In step (3), the heating rate is 4-6°C / min, and the cooling rate is 2-3°C / min.

9. A lithium-rich manganese-based positive electrode composite material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the lithium-rich manganese-based positive electrode composite material according to claim 9 in the preparation of electrode materials or lithium-ion batteries.

Citation Information

Patent Citations

  • High-capacity nickel-cobalt lithium manganate based composite positive electrode material and preparation method thereof

    CN108899502A

  • Preparation method of lithium-rich manganese-based composite material, positive electrode material and lithium ion battery

    CN113104905A

  • Boron gradient doped single crystal lithium-rich manganese-based material (at) Li3BO3 composite material and preparation and application thereof

    CN118136796A

  • Method for repairing surface structure of high-nickel positive electrode material, high-nickel positive electrode material obtained therefrom, and lithium ion battery

    WO2021114746A1